Stevens’ forgotten crossroads: the divergent measurement traditions in the physical and psychological sciences from the mid-twentieth century - McGrane, Joshua A. (Frontiers in Psychology, 2015)
The late 19th and early 20th Centuries saw the consolidation in physics of the three main traditions that predominate in discussions of measurement theory. These are: (i) the systematic tradition pioneered by Maxwell; (ii) the representational tradition pioneered by Campbell; and (iii) the operational tradition pioneered by Bridgman (1927). These divergent approaches created uncertainty about the nature of measurement in the physical sciences and provided Stevens (1946) with an opportunity and rationale to, in effect, reinvent the definition of scientific measurement. Stevens appropriated the representational and operational traditions as the sole basis for his definition of measurement, excluding any place for the systematic approach. In committing to Stevens’ path, the psychological sciences were blinded to the advances made in metrology, the establishment of the International System (SI) and the standard units contained within this system. These advances were only possible due to the deep conceptual and instrumental connections between the system of physical units and the body of physical theory and laws developed over the preceding centuries. It is argued that if the psychological sciences are to ever achieve equivalent methodological advances, they must bridge this ‘metrological gap’ created by Stevens’ measurement crossroads and understand the ways in which the systematic approach advanced measurement. This means that psychological measurement needs to be de-abstracted, rid of operational rules for numerical assignment and set upon a foundation of quantitative theory, definition and law. In the absence of such theoretical foundations, claims of measurement in the psychological sciences remain a methodological chimera.